Dampak Perjanjian Sepihak Terhadap Penyelesaian Kredit Macet - Mulyadi Mulyadi; Rohadi Rohadi; Sarip Sarip (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2021)
Cooperatives occupy a very respectable position in the Indonesian economy. Etymologically, a cooperative is an association or economic organization consisting of people or entities that provide freedom of entry and exit as members. With the existence of an institution in the form of a cooperative such as the example of the Mekar Mandiri cooperative which collects funds from its members then distributes the funds back to the cooperative members and the general public and creates problems, namely what are the factors that cause bad credit in the Mekar Mandiri Cooperative. And how are the efforts to resolve bad loans at the Mekar Mandiri Cooperative. In the research to compile this journal using the type of empirical legal research, law is conceptualized as an empirical phenomenon that can be observed in everyday life, the type of approach used for writing this journal uses a fact approach and a statutory approach. This journal research is descriptive in nature aimed at accurately describing whether or not there is a relationship between the results of the study stating the factors causing the occurrence of bad loans in the Mekar Mandiri Cooperative Keywords: Cooperative, Credit, Agreement.